PENERAPAN PELATIHAN SIAGA BENCANA DALAM MENINGKATKAN PENGETAHUAN, SIKAP, DAN TINDAKAN KOMUNITAS SMA NEGERI 5 BANDA ACEH - Ramli Daud Daud; Sri Adellia Sari; Sri Milfayetty; M. Dirhamsyah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2014)
Abstract: A major contributor to many victims of the earthquake is the lack of public knowledge about disasters and their readiness in anticipation of disaster. School is one of the sciences of transformation media are most effective in absorbing and applying knowledge of disaster preparedness by using appropriate methods and correct. Therefore, the purpose of this study is: 1 ) get a model of disaster preparedness training to improve the knowledge , attitudes , and action of community SMAN 5 Banda Aceh, and 2 ) obtain data on the effectiveness of the training model of the earthquake disaster alert to the increased preparedness of community SMAN 5 Banda Aceh. This research is Classroom Action Research (CAR) conducted in two cycles is descriptive qualitative. Subjects in the first cycle were 30 and totaled 26 in the second cycle, consisting of principals, teachers, students, security guards, cafeteria guard, and guard the school. Data collected by means of observation before and during training to support training in the form of field notes, questionnaire responses to determine aspects of knowledge, attitudes and actions as well as community response to training, and documentation in the form of photos and videos as training supporting data. Results of first cycle studies, the percentage of the average knowledge of the school community was 75%, while in the second cycle increased by 21. 5%. In addition, increased 20. 2% in the second cycle occurs on average percentage for the school community preparedness measures be 97. 1%, and 85. 2% increase from the first cycle to 97. 1% in the second cycle of the average percentage of the attitude of the school community. The increase also occurred in response to the community emergency response training earthquake as a whole is equal to 4. 8% from 79. 1% to 83. 9% in the second cycle. The results of this study concluded that the disaster preparedness training with direct practice model mimics the action of such an earthquake could improve preparedness of community SMAN 5 Banda Aceh with increased knowledge about the earthquake, more appropriate attitudes to earthquakes as well as the more appropriate action in the face of an earthquake.  Keywords: training, knowledge, attitudes, actionspreparedness, earthquake